Pediatric Palliative Care in the Heart Failure, Ventricular Assist Device and Transplant Populations: Supporting Patients, Families and Their Clinical Teams - Kyle D. Hope; Priya N. Bhat; William J. Dreyer; Barbara A. Elias; Jaime L. Jump; Gina Santucci; Natasha S. Afonso; Margaret R. Ninemire; Barbara-Jo Achuff; Erin M. Kritz; Sharada H. Gowda; Kriti Puri (MDPI AG, 2021)
Heart failure is a life-changing diagnosis for a child and their family. Pediatric patients with heart failure experience significant morbidity and frequent hospitalizations, and many require advanced therapies such as mechanical circulatory support and/or heart transplantation. Pediatric palliative care is an integral resource for the care of patients with heart failure along its continuum. This includes support during the grief of a new diagnosis in a child critically ill with decompensated heart failure, discussion of goals of care and the complexities of mechanical circulatory support, the pensive wait for heart transplantation, and symptom management and psychosocial support throughout the journey. In this article, we discuss the scope of pediatric palliative care in the realm of pediatric heart failure, ventricular assist device (VAD) support, and heart transplantation. We review the limited, albeit growing, literature in this field, with an added focus on difficult conversation and decision support surrounding re-transplantation, HF in young adults with congenital heart disease, the possibility of destination therapy VAD, and the grimmest decision of VAD de-activation.